Critical Role of Glycogen Synthase Kinase-3β in Regulating the Avian Heterophil Response to Salmonella enterica Serovar Enteritidis - Kogut, Michael H.; Swaggerty, Christina L.; Chiang, Hsin-I; Genovese, Kenneth J.; He, Haiqi; Zhou, Huaijun; Arsenault, Ryan J. (Frontiers in Veterinary Science, 2014)
A microarray-assisted gene expression screen of chicken heterophils revealed glycogen synthase kinase-3β (GSK-3β), a multifunctional Ser/Thr kinase, to be consistently up-regulated 30-180 min following stimulation with Salmonella enterica serovar Enteritidis (S. Enteritidis). The present study was designed to delineate the role of GSK-3β in regulating the innate function of chicken heterophils in response to S. Enteritidis exposure. Using a specific GSK-3β ELISA assay, 30 min after infection with S. Enteritidis, heterophils had a significant decrease in total GSK-3β, but a significant increase in phosphorylated GSK-3 (Ser9). By 60 min post-infection, there was no difference in the amount of phosphorylated GSK-3β (Ser9) in either the uninfected and infected heterophils. S. Enteritidis interaction with heterophils alters GSK-3 activity by stimulating phosphorylation at Ser9 and that peaks by 30 min post-infection. Further, inhibition of GSK3β with lithium chloride resulted in a significant decrease in NF-κB activation and expression of IL-6, but induces a significant increase in the expression of the anti-inflammatory cytokine, IL-10. Using a phospho-specific antibody array confirmed the phosphorylation of GSK-3β (Ser9) as well as the phosphorylation of the downstream cytokine-activated intracellular signaling pathway involved in stimulating immune responses, IκB, the IκB subunit IKK-β, and the NF-κB subunits p105, p65, and c-Rel. Our data revealed that the phosphorylation of GSK-3β (Ser9) is responsible for inducing and controlling an innate response to the bacteria. Our findings suggest that the repression of GSK-3 activity is beneficial to the host cell and may act as a target for treatment in controlling intestinal colonization in chickens. Further experiments will define the in vivo modulation of GSK-3 as a potential alternative to antibiotics in salmonella and other intestinal bacterial infections.